Therapeutic Strategies against Biofilm Infections - Mishra, Sonal; Gupta, Amit; Upadhye, Vijay; Singh, Suresh C.; Sinha, Rajeshwar P.; Häder, Donat-Peter (Life, 2023)
A biofilm is an aggregation of surface-associated microbial cells that is confined in an extracellular polymeric substance (EPS) matrix. Infections caused by microbes that form biofilms are linked to a variety of animals, including insects and humans. Antibiotics and other antimicrobials can be used to remove or eradicate biofilms in order to treat infections. However, due to biofilm resistance to antibiotics and antimicrobials, clinical observations and experimental research clearly demonstrates that antibiotic and antimicrobial therapies alone are frequently insufficient to completely eradicate biofilm infections. Therefore, it becomes crucial and urgent for clinicians to properly treat biofilm infections with currently available antimicrobials and analyze the results. Numerous biofilm-fighting strategies have been developed as a result of advancements in nanoparticle synthesis with an emphasis on metal oxide np. This review focuses on several therapeutic strategies that are currently being used and also those that could be developed in the future. These strategies aim to address important structural and functional aspects of microbial biofilms as well as biofilms’ mechanisms for drug resistance, including the EPS matrix, quorum sensing (QS), and dormant cell targeting. The NPs have demonstrated significant efficacy against bacterial biofilms in a variety of bacterial species. To overcome resistance, treatments such as nanotechnology, quorum sensing, and photodynamic therapy could be used.
CRIS-Team Scopus Importer:2023-01-27
Keywords: biofilm; biofilm infections; drug resistance; EPS matrix; nanoparticles; quorum sensing